Exploring the depths of on-water training in highly-trained rowing athletes - Watts, S. P.; Binnie, M. J.; Goods, P. S.; Hewlett, J.; Peeling, P. (European Journal of Sport Science, 2024)
This investigation examined the association between on-water rowing stroke-rate (SR), velocity and heart-rate (HR) in highly trained rowers (n = 8 male; n = 8 female and 19.3 ± 1.1 year) over a 4-month real-world (i.e., variable environment and boat class) training period. On-water SR, prognostic velocity (percent of world's best velocity) and HR were captured for 1453 sessions via smart-watch and chest-strap HR monitor. Data was filtered and smoothed with individual HR training zones identified (T1-T5). Linear mixed modeling and an overlapping index (urn:x-wiley:17461391:media:ejsc12069:ejsc12069-math-0001) were used to assess differences in SR and prognostic velocity between HR zones. Correlation coefficient (r) was used to assess the SR and prognostic velocity relationship and progression of prognostic velocity at a SR of 20spm over time. There were significant differences in SR and prognostic velocity between HR zones (T1>T2>T3>T4>T5, p < 0.001); however, data overlap between adjacent zones was substantial for both variables (urn:x-wiley:17461391:media:ejsc12069:ejsc12069-math-0002 = 0.69-0.85; prognostic velocity: urn:x-wiley:17461391:media:ejsc12069:ejsc12069-math-0003 = 0.46-0.86). A significant, positive correlation (r = 0.50 and p < 0.001) between SR and prognostic velocity was found. Progression of prognostic velocity at SR 20spm over the study duration was trivial (r = -0.01 and p = 0.71). Variables commonly used to prescribe and describe on-water rowing training showed large variability in a real-world training environment impacting the ability to accurately monitor training performance and progression.